1997
DOI: 10.1055/s-0038-1656041
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Clot Lysis as a Potential Indicator of Thrombus Resistance to Fibrinolysis – Study in Healthy Subjects and Correlation with Blood Fibrinolytic Parameters

Abstract: SummaryUsing an in vitro model of clot lysis, the individual response to a pharmacological concentration of recombinant tissue plasminogen activator (rt-PA) and the influence on this response of the physiological variations of blood parameters known to interfere with the fibrinolytic/thrombolytic process were investigated in 103 healthy donors. 125I-fibrin labelled blood clots were submersed in autologous plasma, supplemented with 500 ng/ml of rt-PA or solvent, and the degree of lysis was determined after 3 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…4,5,22 However, the majority of platelet PAI-1 is inactive, 3,22 and several groups have concluded that PAI-1 does not contribute substantially to platelet-dependent inhibition of clot lysis in vitro when tPA is present in pharmacological concentrations. 7,8,10 Therefore, our studies, which strongly support an important role of PAI-1 in arterial thrombolysis resistance, underscore the importance of in vivo experiments in defining protein function. We hypothesize that the discordant effects of PAI-1 on clot lysis in vitro and in vivo are explained primarily by 2 factors.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…4,5,22 However, the majority of platelet PAI-1 is inactive, 3,22 and several groups have concluded that PAI-1 does not contribute substantially to platelet-dependent inhibition of clot lysis in vitro when tPA is present in pharmacological concentrations. 7,8,10 Therefore, our studies, which strongly support an important role of PAI-1 in arterial thrombolysis resistance, underscore the importance of in vivo experiments in defining protein function. We hypothesize that the discordant effects of PAI-1 on clot lysis in vitro and in vivo are explained primarily by 2 factors.…”
Section: Discussionsupporting
confidence: 68%
“…7,8 Furthermore, the very high plasma concentrations of tPA attained during thrombolytic therapy have been predicted to overcome the inhibitory effects of plasma and thrombus-associated PAI-1. 9,10 The true role of PAI-1 in regulating the clearance of platelet-rich thrombi can only be assessed by in vivo experiments. Mice deficient in PAI-1 have been generated by gene targeting.…”
mentioning
confidence: 99%
“…Final concentrations of tPA or nanoagent (0 – 30 nM) were calculated based on their total protein amount and a molecular weight of 68 kDa. The degree of lysis was measured at 1 h, 2 h and 3 h of incubation by γ-counting of supernatant (100 μl) and the fractional fibrinolysis was determined as described [24, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…A wide range of clinically relevant concentrations of minocycline (0–30 μg/ml) were added to the supernatant, and clot lysis was immediately initiated by t-PA 2nM (Activase; Genentech). The degree of fibrinolysis was measured at various times of incubation by counting the percent soluble 125 I-fibrin degradation products [15, 16] . The kinetic parameters of amidolysis were measured in the presence or absence of minocycline with H-D-isoleucyl-L-prolyl-L-arginine-p-nitroanilide dihydrochloride (S-2288; Chromogenic) as substrate.…”
Section: Methodsmentioning
confidence: 99%